ANTIDIABETIC ACTIVITIES OF KEMUNING LEAF EXTRACTS (Murraya paniculata) AND MORINGA LEAF (Moringa oleifera) IN DIABETIC RATS - Susilo Margining Raharjo; Titik Sunarni; Nuraini Harmastuti (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Diabetes mellitus is a metabolic disorder characterized by hyperglycemia. The development of diabetic complications plays a pathological role in increasing Reactive Oxygen Species (ROS) levels, which induce oxidative stress. The aim of this study was to examine the antidiabetic activities of kemuning and moringa leaves based on glucose, SOD, and GPx levels, and the protective activity of pancreatic cells in STZ-NA-induced rats. The kemuning and moringa leaves were dried, finely powdered, and extracted by the remaceration method using 96% ethanol. The test was carried out on 30 rats that were divided into 6 treatment groups, namely the normal control group, negative control, positive control (glibenclamide), extract dose of 76.5 mg. /200 g BW : 6.5 mg/200 g BW, 114.75 mg/200 g BW : 3.25 mg/200 g BW and 38.25 mg/200 g BW : 9.75 mg/ 200 g BW. The antidiabetic test was carried out using STZ-NA, glucose levels were measured, and SOD and GPx levels in the liver supernatants were measured. Cell protection was tested using the cell damage score method. The data obtained were analyzed using one-way ANOVA variance. The results showed that kemuning and moringa leaves at a dose of 38.25 mg/200 g BW: 9.75 mg/200 g BW were able to lower blood glucose levels, increase the activity of SOD and GPx, and protect pancreatic cell damage in STZ-NA rats. Keywords: Antidiabetic, antioxidant, moringa, kemuning, SOD, GPx